2014
DOI: 10.1093/rheumatology/keu300
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow in the hands of a predefined homogeneous systemic sclerosis population: the presence of digital ulcers and the improvement with bosentan

Abstract: https://www.clinicaltrialsregister.eu/ (EudraCT number 2010-023908-27).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…9 Endothelin receptor antagonists are approved for the prevention of DU recurrence with improved hand functionality and better functional and vital prognosis based on the results of the RAPIDS-1 and RAPIDS-2 trials. 2,4,6,12,13 Other studies have shown that bosentan treatment increased the fingertip blood flow in patients with low perfusion in its initial stages, helping in the process of remodeling the capillary microcirculation. 2,5 Short-acting antiplatelet and anticoagulant therapy should be considered, although there is no strong evidence of its efficacy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…9 Endothelin receptor antagonists are approved for the prevention of DU recurrence with improved hand functionality and better functional and vital prognosis based on the results of the RAPIDS-1 and RAPIDS-2 trials. 2,4,6,12,13 Other studies have shown that bosentan treatment increased the fingertip blood flow in patients with low perfusion in its initial stages, helping in the process of remodeling the capillary microcirculation. 2,5 Short-acting antiplatelet and anticoagulant therapy should be considered, although there is no strong evidence of its efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…2,4,6,12,13 Other studies have shown that bosentan treatment increased the fingertip blood flow in patients with low perfusion in its initial stages, helping in the process of remodeling the capillary microcirculation. 2,5 Short-acting antiplatelet and anticoagulant therapy should be considered, although there is no strong evidence of its efficacy. 4 There is strong theoretical support for the use of antiplatelet agents in SSc and a consensus on the practical approach for prescription, being recommended in all patients with chronic digital ischemia.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In 40% of cases they are observed within the first year, and in 70% within 5 years from the moment of SSc clinical presentation other than Raynaud's phenomenon [2]. They appear in 30% of patients with limited SSc (lSSc) and in almost 60% of patients suffering from diffuse SSc (dSSc) [3][4][5]. Digital ulcers appear more often in male patients and smokers, in whom Raynaud's phenomenon appeared shortly before SSc diagnosis, Scl-70 antibodies are confirmed, acute-phase proteins concentration is elevated, or who suffer from pulmonary hypertension [6].…”
mentioning
confidence: 99%